Assessment of pesticide use in major vegetables from farmers’ perception and knowledge in Dhading district, Nepal - Bhandari, Sandesh; Paneru, Sushma; Pandit, Shailesh; Rijal, Sramika; Manandhar, Hira Kaji; Ghimire, Bishnu Prasad (Journal of Agriculture and Natural Resources, 2020)
A field study was carried out to assess the pesticide use status in major vegetable crops from farmers’ perception and knowledge in Dhading, Nepal in 2019. Field study was carried with 100 commercial farmer’s using semi-structure questionnaire by face to face interview. This study was analyzed by categorization of farmers into small holder (51) and large holder (49) groups on the basis of mean area of vegetable cultivation (6.48 ropani). The highest amount of pesticides is needed in tomato in both large holders and small holders according to the farmer’s experience. Among the study farmer’s, 41% of them spray the pesticides by making a cocktail or mixed method and 56%  follow the waiting period of 3-5 days in both of the cases. A significant positive correlation was found at 5% level of significance between the knowledge and practice pattern of waiting period of the pesticides and negative correlation was found between the Personal Protective equipment score and health hazard score. Headache was the major health hazards faced by the farmers which was higher in small holders (66.7%) as compared to the large holders (46.9%). Mask was the most used PPE by the farmer’s i.e. by 83% in overall. Fourty three percent of the farmer’s throw the pesticide containers in secret place after using of it.The use of PPE was seen lower in small holders as compared to the large holders. This study reveals the necessities of suitable program and policies regarding the knowledge, safe handling and use of pesticide among the farmer’s level.